THE IMPACT OF ENGLISH AS A GLOBAL LANGUAGE (International journal of artificial intelligence, 2025)
English has emerged as the dominant global language, influencing various aspects of communication, education, business, and cultural exchange. This study examines the impact of English as a global language by analyzing its role in international relations, economic development, and linguistic diversity. The research employs a qualitative approach, reviewing existing literature and case studies to assess both the benefits and challenges associated with the widespread use of English. The findings indicate that English facilitates global communication and economic opportunities; however, it also contributes to the erosion of minority languages and cultural identities. The discussion highlights the implications of English dominance on linguistic diversity and proposes strategies for promoting multilingualism while maintaining the advantages of a common global language. The study concludes that while English enhances global connectivity, efforts to preserve linguistic diversity remain essential.